2012
DOI: 10.1080/09540121.2012.701716
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of perceived social support on health-related quality of life in persons living with HIV/AIDS

Abstract: Research has established a link between perceived social support and health-related quality of life (HRQOL) among persons living with HIV/AIDS. However, little is known about the ways through which social support influences HRQOL. This study examined the direct and indirect effects of perceived social support on physical and mental HRQOL in a sample of 602 adults living with HIV in Ontario, Canada. Participants completed the Medical Outcomes Study-HIV (MOS-HIV) health survey, the MOS-HIV Social Support Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
94
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 47 publications
12
94
0
3
Order By: Relevance
“…For example, Friedland et al, (1996) found that emotional support was a statistically significant factor in determining quality of life for individuals living with HIV, and note that support services that "bridge the gap between informal and formal" (e.g., a camp experience) may be particularly beneficial (p. 28). Similarly, Ashton et al reported that satisfaction with social support was linked to a lower level of progression of HIV-related health symptoms (2005); Bekele et al (2013) found that perceived social support directly affected both physical and mental health, as well as mediating depressive symptoms; and Clingerman (2004) found that social support provided by friends was positively linked to health-related quality of life. Extrapolating these findings, it is therefore theoretically possible that attending a campwhich has proven in this study to act as a significant form of social support -may have some effects on health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Friedland et al, (1996) found that emotional support was a statistically significant factor in determining quality of life for individuals living with HIV, and note that support services that "bridge the gap between informal and formal" (e.g., a camp experience) may be particularly beneficial (p. 28). Similarly, Ashton et al reported that satisfaction with social support was linked to a lower level of progression of HIV-related health symptoms (2005); Bekele et al (2013) found that perceived social support directly affected both physical and mental health, as well as mediating depressive symptoms; and Clingerman (2004) found that social support provided by friends was positively linked to health-related quality of life. Extrapolating these findings, it is therefore theoretically possible that attending a campwhich has proven in this study to act as a significant form of social support -may have some effects on health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, social support was significantly associated with a variety of other factors that may affect quality of life: employment status, income, and housing-related discrimination (p. 340). Ashton et al, (2005), Friedland, et al, (1996 and Bekele et al, (2013) all cite as an implication the need for increased "informal support" services, such as buddy lines and drop-in centres (Ashton et al, 2005 p. 28). …”
Section: Hiv Social Support and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…O suporte social consiste na satisfação da pessoa com o apoio que tem recebido da rede de relações sociais, ou seja, de que forma as pessoas oferecerem condições que auxiliam no TARV, e pode ser dividido em duas categorias: o suporte social instrumental e o suporte social emocional. O primeiro, refere-se à disponibilização de ajuda em situações operacionais do cotidiano, tais como apoio financeiro e/ou material; o segundo, aos comportamentos de escutar, de prover atenção ou fazer companhia para que a pessoa infectada pelo HIV possa se sentir estimada e/ou cuidada [14][15][16].…”
Section: Introductionunclassified
“…The importance of the social network and the support it provides for individuals' well-being and quality of life (QoL) has been widely reported in the HIV literature (Bekele et al, 2013;Chesney, Chambers, Taylor, & Johnson, 2003;Mavandadi, Zanjani, Ten Have, & Oslin, 2009), although less frequently among those with HIV who are aged 50 and older (Emlet, Fredriksen-Goldsen, & Kim, 2013). As this segment of the HIV population is steadily growing worldwide and is an emergent issue in Finland (National Institute for Health and Welfare [THL], 2015), acknowledging the importance of social networks in the older population may provide a good baseline for health and social care interventions aimed at promoting healthy ageing with HIV.…”
Section: Introductionmentioning
confidence: 99%